2006
DOI: 10.1097/00001665-200605000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and Hydraulic Mechanisms in Orbital Blowout Fractures

Abstract: Since the first description of orbital blowout fractures, there has been much confusion as to their etiology. Two principal mechanisms have been proposed to explain their production, the buckling and the hydraulic mechanisms caused, respectively, by trauma to the orbital rim and the globe of the eye. The aim of this study was to evaluate both mechanisms qualitatively and quantitatively. Our protocol used intact cadavers, quantifiable intraocular pressure, variable and quantifiable force, and quantifiable bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 14 publications
8
62
0
2
Order By: Relevance
“…Increased intraorbital hydraulic pressure does not play a role in blow-in fractures. Recent cadaver studies demonstrated that the buckling mechanism causes small fractures without medial wall involvement, and the hydraulic mechanism causes larger fractures involving both the anterior and posterior parts of the inferior wall [5,14] . It seems that higher coefficient of curvature of the inferior wall in patients with inferior wall fracture is associated with the hydraulic theory of increased hydraulic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intraorbital hydraulic pressure does not play a role in blow-in fractures. Recent cadaver studies demonstrated that the buckling mechanism causes small fractures without medial wall involvement, and the hydraulic mechanism causes larger fractures involving both the anterior and posterior parts of the inferior wall [5,14] . It seems that higher coefficient of curvature of the inferior wall in patients with inferior wall fracture is associated with the hydraulic theory of increased hydraulic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Fujino and Makino [2] described that in order to produce a blowout fracture by hydraulic pressure, a force greater than the forces applied would be necessary to cause the observed buckling of the orbital floor. In contrast, several recent experimental results have shown that the average energy necessary for fracture production by a hydraulic mechanism is close to that of a buckling mechanism [3,4]. In addition to these experiments, Lee [5] reported one case of a blowout fracture caused by a headlock, which supports the pure hydraulic theory.…”
Section: Introductionmentioning
confidence: 75%
“…They also described that if the primary causative factor was an increased hydraulic pressure, a high incidence of ocular injuries would be encountered. On the contrary, some detailed recent experimental results have shown that the average energy necessary for fracture production by a hydraulic mechanism is nearer to that required for the buckling mechanism [3,4,16]. Warwar et al [3] described that both mechanisms contribute to most clinically observed orbital floor fractures and the experimentally measured value required to fracture the orbital floor directly is significantly less than the previously reported energy value required to rupture a human eyeball.…”
Section: Discussionmentioning
confidence: 94%
“…As a study method for facial bone fracture, actual application of impacts on cadavers' orbits might be more convincing than dynamic calculation because reality is superior to simulation. Indeed, the mechanisms of orbital fracture used to be studied on cadavers in the past [13,14]. However, destruction of cadavers is ethically unacceptable nowadays.…”
Section: Methodsmentioning
confidence: 99%